Outbreak of NDM-5-producing Klebsiella variicola in intensive care units: an overlooked pathogen in Argentina? - Francisco González-Espinosa; Diego Marcelo Maurizi; Dina Pedersen; Alejandra Soledad Oriani; Celeste Martinez; Jerson Andrés Martínez Lozano; Gabriel Gutkind; Marcela Radice; Daniela Cejas (Microbiology Spectrum)
ABSTRACT Here, we characterized the first Klebsiella variicola isolates responsible for an outbreak in the intensive care units (ICUs) in a hospital in Argentina. Five isolates recovered from inpatients and sinks at the ICUs of one hospital in Bahia Blanca City were included. Identification and antimicrobial susceptibility tests were performed using an automated system (Phoenix). Besides, they were identified using two mass spectrometry systems (Bruker Daltonics and BioMérieux) and a multiplex-PCR for Klebsiella pneumoniae complex identification. Whole-genome sequencing (WGS) was conducted to confirm bacterial identification and to analyze their resistome and mobilome. Additionally, clonal and phylogenetic relationships were investigated among local and worldwide isolates. Based on the Phoenix system, all isolates were identified as K. pneumoniae and resistant to last-line antibiotics, consistent with a difficult-to-treat phenotype (DTR). All of them carried blaNDM-5. The isolates were identified as K. variicola by one of the Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) systems and by multiplex-PCR. WGS confirmed all isolates as K. variicola subsp. variicola belonging to ST3029, an infrequent lineage among the genomes analyzed. They displayed fewer than six SNPs, which corresponded to a unique clone, and the phylogenetic analysis exhibited a close relationship with isolates recovered from an environmental source in Brazil.IMPORTANCEKlebsiella variicola is an emerging pathogen in humans belonging to the K. pneumoniae complex. K. variicola identification by classical biochemical methods is challenging, and it is often misidentified as K. pneumoniae. K. variicola has been isolated from diverse clinical samples such as blood, respiratory, and urinary tract infections, and in different environments. The present work describes for the first time K. variicola isolates recovered in Argentina, which were resistant to the last line of antibiotics consistent with a difficult-to-treat phenotype and responsible for a hospital outbreak. In addition, the phylogenetic analysis exhibited a close relationship to environmental isolates from Brazil.